2000
DOI: 10.1007/s001250050034
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of progression of macrovascular diseases after kidney or pancreas and kidney transplantation in diabetic patients with end-stage renal disease

Abstract: Simultaneous pancreas-kidney transplantation (SPKT) has become the therapy of choice in patients with Type I (insulin-dependent) diabetes mellitus who have end-stage renal disease. During the last decade graft and patient survival have been improved, the 1-year pancreas graft survival rate is currently at 81 % for SPKT [1].Several studies have shown that diabetic retinopathy and peripheral neuropathy are positively influenced by pancreas transplantation [2,3]. A recent study also showed that pancreas transplan… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
17
0

Year Published

2000
2000
2015
2015

Publication Types

Select...
6
4

Relationship

1
9

Authors

Journals

citations
Cited by 36 publications
(17 citation statements)
references
References 11 publications
0
17
0
Order By: Relevance
“…There are very few studies that have actually assessed cardiovascular outcomes comparing SPK with KTA. In a small study, Biesenbach et al [32] showed a reduction in risk factors for the development of macroangiopathy but failure to halt progression of macrovascular diseases (CAD, CBVD and PAD) in 11 SPK recipients compared with ten KTA (kidneys from deceased donors) recipients with at least 2 year functioning grafts and a follow-up time of nearly 6 years. However, later on and with a longer follow-up time, the same group showed that the progression of macrovascular diseases was significantly lower in recipients with a functioning SPK graft compared with KTA recipients [33].…”
Section: Discussionmentioning
confidence: 99%
“…There are very few studies that have actually assessed cardiovascular outcomes comparing SPK with KTA. In a small study, Biesenbach et al [32] showed a reduction in risk factors for the development of macroangiopathy but failure to halt progression of macrovascular diseases (CAD, CBVD and PAD) in 11 SPK recipients compared with ten KTA (kidneys from deceased donors) recipients with at least 2 year functioning grafts and a follow-up time of nearly 6 years. However, later on and with a longer follow-up time, the same group showed that the progression of macrovascular diseases was significantly lower in recipients with a functioning SPK graft compared with KTA recipients [33].…”
Section: Discussionmentioning
confidence: 99%
“…In an investigation of carotid intimal thickness in pancreas transplantation candidates and in pancreas transplant recipients 4‐yr post‐transplant, the latter group had lower thickness, suggesting a beneficial effect of the procedure, when successful (18). In a small Austrian series, the extent of cardiovascular disease was classified in SPK and kidney‐alone transplant recipients at baseline and for a follow‐up time of 5 yr on average (16). No difference in the progression of macrovascular manifestations was seen.…”
Section: Discussionmentioning
confidence: 99%
“…In our study we compared the progression of vascular diseases in type 1 diabetic patients with KTA and SPKT over a mean period of 10 years. In an earlier study with patients with at least 2‐year functioning grafts there was no significant difference between the prevalence of vascular diseases 5 years after SPKN and KTA [14]. Hence, it was concluded that SPKT reduces cardiovascular risk factors but does not halt progression of macrovascular diseases during the first 5 years after transplantation.…”
Section: Introductionmentioning
confidence: 96%